ChemInform Abstract: Synthesis, Structure, and Electrochemical Performance of High Capacity Li2Cu0.5Ni0.5O2 Cathodes. Issue 52 (10th December 2015) - Ruther, Rose E.; Zhou, Hui; Dhital, Chetan; Saravanan, Kuppan; Kercher, Andrew K.; Chen, Guoying; Huq, Ashfia; Delnick, Frank M.; Nanda, Jagjit
Abstract: The title compound is prepared by coprecipitation from aqueous solutions of Cu(NO3 )2, Ni(NO3 )2, NH4 OH, and LiOH (50 °C, 3 h).